2018
DOI: 10.1038/s41698-017-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator-stimulated phosphoprotein promotes liver metastasis of gastrointestinal cancer by activating a β1-integrin-FAK-YAP1/TAZ signaling pathway

Abstract: Extracellular matrix (ECM)-induced β1-integrin-FAK signaling promotes cell attachment, survival, and migration of cancer cells in a distant organ so as to enable cancer metastasis. However, mechanisms governing activation of the β1-integrin-FAK signaling remain incompletely understood. Here, we report that vasodilator-stimulated phosphoprotein (VASP), an actin binding protein, is required for ECM–mediated β1-integrin-FAK-YAP1/TAZ signaling in gastrointestinal (GI) cancer cells and their liver metastasis. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…HT29 human colorectal cancer cells and Lewis lung carcinoma cells (LLCs) were purchased from ATCC. L3.6 human pancreatic cancer cells were provided by Dr. Raul Urrutia (Medical College of Wisconsin) (20) and LX2 cells were from Dr. Scott Friedman (Icahn School of Medicine at Mount Sinai). Cells were authenticated by Genetica.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HT29 human colorectal cancer cells and Lewis lung carcinoma cells (LLCs) were purchased from ATCC. L3.6 human pancreatic cancer cells were provided by Dr. Raul Urrutia (Medical College of Wisconsin) (20) and LX2 cells were from Dr. Scott Friedman (Icahn School of Medicine at Mount Sinai). Cells were authenticated by Genetica.…”
Section: Methodsmentioning
confidence: 99%
“…Subcutaneous HSC/tumor injection into nude mice and in vivo xenogen imaging were done as described (23, 25). LLCs were implanted into p300 F/F cre mice by intrasplenic injection (20) and L3.6 cells were injected into SCID mice by portal vein injection (23, 24). Details about control and p300 F/F cre mice, and tumor injection protocols are in Supplementary Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…In colon cancer cells phosphorylation of VASP at Ser 239 suppressed the formation of filopodia and invadopodia inhibiting the migration of cancer cells [236]. In patients with gastrointestinal cancer VASP is required for the ECM-mediated β1-integrin-FAK-YAP1/TAZ signaling, and high levels of protein expression in colorectal cancers pancreatic ductal adenocarcinomas significantly correlated with liver metastasis and reduced patient survival [237]. Wang et al showed that miRNA-610 inhibits the invasion of gastric cancer cells by suppressing the expression of VASP, which could be used therapeutically to inhibit gastric cancer progression and metastasis [238].…”
Section: Ena/vasp In Cancermentioning
confidence: 99%
“…Integrins overexpressed in gastrointestinal cancer are known to regulate tumor progression. For instance, ECM-mediated integrin β1 promotes liver metastasis of gastrointestinal cancer through focal adhesion kinase (FAK)-yes-associated protein 1 (YAP1)/tafazzin (TAZ) signaling, which is enhanced by vasodilator-stimulated phosphoprotein (VASP) [116]. In addition, ECM1-mediated integrin β4 promotes EMT and glucose metabolism via SOX2/HIF-1α signaling in gastric cancer [117] and modulates epidermal growth factor receptor (EGFR) signaling to induce gefitinib chemoresistance [118].…”
Section: Integrinsmentioning
confidence: 99%